Short communication: Algal genotypes in White Syndrome infected coral Acropora muricata from the Karimunjawa Islands, Indonesia - Diah Permata Wijayanti; Maula Nadia; Elis Indrayanti; Dwi Haryanti; Muggi Bachtiar (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wijayanti DP, Nadia M, Indrayanti E, Haryanti D, Bachtiar M. 2021. Short communication: Algal genotypes in White Syndrome infected coral Acropora muricata from the Karimunjawa Islands, Indonesia. Biodiversitas 23: 415-423. The physiological equilibrium of the coral holobiont may help the corals to survive under various environmental threats. The symbiont genotype is thought to play an important role in the host's susceptibility to thermal stress and coral disease incidence. We identified the Symbiodiniaceae diversity of coral Acropora muricata infected by White Syndrome (WS). Samples were collected from Cemara Kecil Island and Barakuda Beach, Kemujan Island, Karimunjawa Islands. We applied DNA barcoding of 28S nuclear ribosomal RNA gene of the healthy colonies, healthy tissue, and lesions of diseased colonies to perform their symbiont type identification. There were two different symbiont types observed from the phylogenetic analysis, which formed two clades. A clade consisting all Cemara Kecil Island samples while the other with all Barakuda Beach samples except for one. All samples harbored symbiont types from the genus Cladocopium. The members of the genus were reported to have various physiological properties which may support the host resilience when facing the disease. A robust study is needed to reveal the influence of symbiont genotypes on the occurrence of coral disease and the susceptibility of the coral host.